Religious Education in the Family Environment According to Nurcholish Madjid: Pendidikan Agama di Lingkungan Keluarga Menurut Nurcholish Madjid - Farista, Rizal; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2021)
Nurcholish Madjid is a Muslim scholar who has contributed thoughts about religious education in the family environment. This study aims to describe Nurcholish Madjid's thoughts about religious education in the family environment. This research uses library research method. The primary data sources in this study were books by Nurcholish Madjid, while the secondary data sources were taken from various books, journals, articles that still have relevance to the research topic. To describe Nurcholis Madjid's views on religious education in the family environment, this study uses an interpretation approach. In this study, Nurcholish Madjid's interpretation of religious education is found, which is defined as a series of educational processes to develop children into human beings who are close (taqarrub) to Allah Subhanahu Wa Ta'ala and have al-karimah morality. In its implementation, this achievement is carried out by exemplary methods from parents which are manifested through inculcating Islamic values ​​in all interactions with the child